Red Palm Oil as a Source of Natural Antioxidants: a Review of its Potential in the Development of Functional Foods - Wahid Wirawan; La Ode Alwi; Eko Aprianto Johan; Wira Yuda (Journal of Food and Agricultural Product, 2026)
Red Palm Oil (RPO) is a natural antioxidant source rich in carotenoids, particularly beta-carotene, and vitamin E, with significant potential for development as a functional food ingredient. However, the primary challenge in utilizing RPO is the degradation of its bioactive compounds, such as carotenoids and vitamin E, during processing and storage. This degradation can affect the nutritional quality and health benefits of products containing RPO. This article is a narrative review aimed at evaluating the potential of Red Palm Oil (RPO) as a natural antioxidant source in the development of functional foods. The article also identifies the key challenges in maintaining the stability of bioactive compounds and reviews various cutting-edge technological solutions that can enhance its stability, which have not been widely addressed in the existing literature. The proposed approaches include the use of low-temperature processing technologies, microencapsulation, and nanoemulsion to preserve the nutritional quality and bioactive compound effectiveness in RPO. The findings indicate that while RPO has a high content of carotenoids and vitamin E, the stability of these compounds heavily depends on the processing methods used. The application of proper processing technologies can enhance RPO’s potential in functional food products, contributing to the prevention of degenerative diseases such as cardiovascular diseases, diabetes, and neurodegenerative disorders. In conclusion, RPO has significant potential in the functional food industry; however, further innovations in processing technologies and marketing strategies are required to optimize its utilization. Keywords: Red Palm Oil, antioxidants, carotenoids, vitamin E, functional foods